SUSTAINABLE CONSUMPTION IN CONSUMER BEHAVIOUR OF POLISH SENIORS (REPORT FROM OWN RESEARCH) - Zalega, Tomasz (Acta Scientiarum Polonorum. Oeconomia, 2018)
The discussion presented in this study focuses on consumer behaviour of people aged 65+ in Poland that may be classified as sustainable consumption. The article primarily seeks to offer some insight into sustainable consumption within the consumer decision-making process among Polish seniors. The basis for the conclusions is provided by direct research conducted in the form of a survey questionnaire on a sample of 2,537 people aged 65+ in 2014–2015 in 10 Polish cities f various populations and sizes.